2022
DOI: 10.1007/s12237-022-01087-5
|View full text |Cite
|
Sign up to set email alerts
|

Can Coastal Habitats Rise to the Challenge? Resilience of Estuarine Habitats, Carbon Accumulation, and Economic Value to Sea-Level Rise in a Puget Sound Estuary

Abstract: Sea-level rise (SLR) and obstructions to sediment delivery pose challenges to the persistence of estuarine habitats and the ecosystem services they provide. Restoration actions and sediment management strategies may help mitigate such challenges by encouraging the vertical accretion of sediment in and horizontal migration of tidal forests and marshes. We used a process-based soil accretion model (Coastal Wetland Equilibrium Model) combined with a habitat classification model (MOSAICS) to estimate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
4
0
4
Order By: Relevance
“…La restauración de las llanuras aluviales que sirven de hábitat al salmón 194 también beneficia a los seres humanos al reducir la exposición actual y futura de la agricultura y las infraestructuras a las inundaciones provocadas por los efectos combinados del aumento del nivel del mar, las marejadas ciclónicas y la escorrentía de los arroyos 195,196 . Como en las décadas recientes se han eliminado varias presas y otros obstáculos a las áreas históricas de desove, en algunos casos los peces han recolonizado rápidamente los nuevos hábitats accesibles 197,198,199,200 .…”
Section: Capacidad De Adaptación De Los Ecosistemas Y Las Especies Al...unclassified
See 1 more Smart Citation
“…La restauración de las llanuras aluviales que sirven de hábitat al salmón 194 también beneficia a los seres humanos al reducir la exposición actual y futura de la agricultura y las infraestructuras a las inundaciones provocadas por los efectos combinados del aumento del nivel del mar, las marejadas ciclónicas y la escorrentía de los arroyos 195,196 . Como en las décadas recientes se han eliminado varias presas y otros obstáculos a las áreas históricas de desove, en algunos casos los peces han recolonizado rápidamente los nuevos hábitats accesibles 197,198,199,200 .…”
Section: Capacidad De Adaptación De Los Ecosistemas Y Las Especies Al...unclassified
“…Existe amplia evidencia de que la conservación de la diversidad genética y la protección y restauración ecológicas pueden beneficiar los procesos de los ecosistemas y aumentar la capacidad de adaptación de las especies 120,121,122,192,193,194,195,196 . Por ejemplo, la restauración mediante la eliminación de presas y estructuras infranqueables en todo el Noroeste ha restablecido algunos procesos ecológicos e hidrológicos naturales que permiten a los peces anádromos acceder a su hábitat histórico 194,197,198,199,200 .…”
Section: Mensaje Clave 272 Los Ecosistemas Cambian En Respuesta a Los...unclassified
“…Using a wetland elevation model, a habitat model, and many types of data collected in wetlands, scientists found that with more than 1 meter of sea level rise, most salt marsh may transition to sparsely vegetated marsh or mudflat and that the rate of carbon accumulation would decline. 5 Without management intervention, the projected loss of tidal marsh and forested habitat resulting from sea level rise could also affect the base of the salmon food web and salmon growth throughout the estuary. Because Chinook salmon are one of the most estuarine-dependent salmonids, substantial declines in estuarine habitat would imperil this native and highly prized cultural resource.…”
Section: Challenges At Nisqually-climate and Sea Level Risementioning
confidence: 99%
“…However, anthropogenic disturbances at global to watershed scales across the last two centuries have caused dramatic changes in temperature, fluctuations in the thermocline, shoaling of the aragonite saturation horizon, and reduced dissolved oxygen (DO) with depth in marginal seas (Feely et al, 2012). Rising atmospheric CO2 concentration is predicted to result in warmer ocean temperatures, hypoxia, ocean acidification (OA), and extreme weather (Gruber et al, 2012;Melzner et al, 2011;Moritsch et al, 2022;Rykaczewski and Dunne, 2010). OA is the process in which increased levels of atmospheric CO2 dissolve into the ocean resulting in a more acidic environment (Jiang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%